EFFECTS OF FOOTBALL TRAİNİNGS ON TSH, T3 AND T4 HORMONE LEVELS - Sari, Mehmet Akif; Şengün, Nezihe; Pala, Ragıp (Ataturk Universitesi, 2021)
In the current study, the changes in TSH, T3 and T4 hormone levels measured before and after the 8 weeks of football training were examined. The study was conducted in the Fırat University men's football team, 10 volunteer football players with a mean age of (21,90±2,18) years, a sports age average of (10,30±1,70) years, a body weight average of (66,24±8,22) kg, a height average of (175,70±4,69) cm and body mass indexes of (21,37±1,72) kg/m², were participated. A total of 90 minutes of soccer training program (10 minutes of general warm-up, 15 minutes of special warm-up, 10 minutes of pass training, 45 minutes of football-specific coordination, agility, quickness, condition, strength, endurance, tactical training and 10 minutes of cool-down exercises) were applied, 6 days a week for 8 weeks. The data were analyzed with the help of SPSS package program to reveal the differences before and after 8 weeks of training with the tests used to compare the means between the dependent groups. The normality of the data was examined by Shapiro-Wilk test. Those that showed normal distribution among the data were analyzed with the dependent t-test, and those that did not show normal distribution were analyzed with the Wilcoxon test. Statistical significance level was accepted as p<0,05. As a result of the research, it was statistically determined that 8 weeks of football training caused a significant decrease in TSH, T3 and T4 hormone levels (p<0,01). © 2021, Ataturk Universitesi. All rights reserved.
FUTBOL ANTRENMANLARININ TSH, T3 VE T4 HORMON DÜZEYLERİNE ETKİLERİ
Keywords: Football; Hormone; T3; T4; TSH